Pembangunan Dan Keberkesanan Modul Gravi-Stem Terhadap Konsep Alternatif, Kbat Serta Minat Murid Tingkatan 4 Dalam Topik Kegravitian - Roslan, Abdul Halim (2023)
This study aims to develop the Gravi-STEM Module, a Science, Technology, Engineering, and Mathematics (STEM) and Inquiry Based Learning (IBL) integrated module focusing on the topic of gravitation. The Gravi-STEM module was developed comprehensively using the Sidek Module Development Model. This module underwent content validity evaluation by three experts in teaching and learning (T&L) and STEM education. To test its reliability, a pilot study was conducted with 30 secondary school students who completed all activities specified in the module. The students' feedback was gathered through a reliability questionnaire. The experts' consensus deemed the module to have good content validity with a coefficient of 0.88 and excellent reliability with a coefficient of 0.95.This study also investigates the effectiveness of the Gravi-STEM Module towards alternative conception, Higher-Order Thinking Skills (HOTS) and interest of form four students in gravitation topic as compared to conventional learning method. Employing a quasi-experimental of non-equivalent groups pre-post test design, purposive sampling and random sampling were used on a sample of 61 Form Four students from two schools involving Batang Padang and Kerian districts. 30 pupils represented the students of the treatment group, while 31 pupils represented the control group pupils.